Modulation of Murine Olivary Connexin 36 Gap Junctions by PKA and CaMKII - Bazzigaluppi, Paolo; Isenia, Sheena C.; Haasdijk, Elize D.; Elgersma, Ype; De Zeeuw, Chris I.; van der Giessen, Ruben S.; de Jeu, Marcel T. G. (Frontiers in Cellular Neuroscience, 2017)
The inferior olive (IO) is a nucleus located in the brainstem and it is part of the olivo-cerebellar loop. This circuit plays a fundamental role in generation and acquisition of coherent motor patterns and it relies on synchronous activation of groups of Purkinje cells (PC) in the cerebellar cortex. IO neurons integrate their intrinsic oscillatory activity with excitatory inputs coming from the somatosensory system and inhibitory feedback coming from the cerebellar nuclei. Alongside these chemical synaptic inputs, IO neurons are coupled to one another via Connexin 36 (Cx36) containing Gap Junctions (GJs) that create a functional syncytium between neurons. Communication between olivary neurons is regulated by these GJs and their correct functioning contributes to coherent oscillations in the IO and proper motor learning. Here, we explore the cellular pathways that can regulate the coupling between olivary neurons. We combined in vitro electrophysiology and immunohistochemistry on mouse acute brain slices to unravel the pathways that regulate olivary coupling. We found that enhancing the activity of the protein kinase A (PKA) pathway and blocking the Ca2+/calmodulin-dependent protein kinase II (CaMK2) pathway can both down-regulate the size of the coupled network. However, these two kinases follow different mechanisms of action. Our results suggest that activation of the PKA pathway reduces the opening probability of the Cx36 gap junctions, whereas inhibition of the CaMK2 pathway reduces the number of Cx36 gap junctions. The low densities of Cx36 proteins and electrical synapses in CaMK2B knock-out mice point towards an essential role for this protein kinase in regulating the density of GJs in the IO, possibly by stabilization and/or bundling of actin. Thus, the level of olivary coupling is a dynamic process and regulated by a variety of co-acting enzymes.